Conserved G-Quadruplex Motifs in Gene Promoter Region Reveals a Novel Therapeutic Approach to Target Multi-Drug Resistance Klebsiella pneumoniae - Shankar, Uma; Jain, Neha; Mishra, Subodh Kumar; Sharma, Tarun Kumar; Kumar, Amit (Frontiers in Microbiology, 2020)
An opportunistic pathogen, Klebsiella pneumoniae is known to cause life-threating nosocomial infection with a high rate of morbidity and mortality. Evolutions of multi-drug-resistant and hyper-virulent strains of K. pneumoniae make the situation worse. Currently, there is no incisive drug molecule available for drug-resistant hyper-virulent K. pneumoniae infection that emphasizes the need for identification of novel and more promising drug targets in K. pneumoniae. Recently, various non-canonical structures of nucleic acids especially G-quadruplex (G4) motifs have been identified as potential therapeutic targets against several human pathogenic bacteria and viruses including Mycobacterium tuberculosis, Streptococcus pneumoniae, human immunodeficiency virus (HIV), Ebola, and Nipah. Therefore, in present study we screened the K. pneumoniae genomes for identification of evolutionary conserved G4 structure-forming motifs as promising anti-bacterial drug targets. Bioinformatics analysis revealed the presence of six highly conserved G4 motifs in the promoter region of five essential genes that play a critical role in nutrient transport and metabolism. Biophysical studies showed the formation of G4 structure by these conserved motifs. Circular Dichroism melting analysis showed the stabilization of these G4 motifs by a well-known G4-stabilizing agent, BRACO-19. The stabilization of these motifs by BRACO-19 was also able to stop the primer extension process, which is an essential phenomenon for expression of the G4-harboring gene. The addition of G4-specific ligand at low micromolar range was observed to be lethal for the growth of this bacteria and negatively controlled the expression of the G4-harboring genes via G4 structure stabilization. These observations strengthen the formation of G4 structures by the predicted G4 motif in vivo, which can be stabilized by G4 ligands like BRACO-19. This stabilization of G4 structures can attenuate the expression of G4-harboring essential genes and thus play a critical role in the regulation of gene expression. Thus, taking all given result in consideration, for the first time, this study showed the new therapeutic avenue for combating K. pneumoniae infection by characterizing the conserved G4 motifs as promising therapeutic targets.